Influence of lifestyle and environmental habits on the health of youth (literature review) (Environment & Health, 2024)
Introduction. The problem of youth health and its value orientations is currently one of the most urgent. Education of a culture of health and positive environmental habits among young people appears as one of the priority tasks of state policy.Goal. Analyze data from scientific sources regarding the impact of lifestyle and environmental habits on the health of young people.Materials and methods. Analytical review of scientific publications was performed using reference databases of scientific libraries Pub Med, Medline and text databases of scientific publishing houses Pub Med, Central, BMJ group, etc. Bibliographic, epidemiological and system analysis methods were used.Review. The analysis of the scientific literature shows that tobacco, alcohol, and energy drinks are quite common in the student environment. It is shown that risk factors, namely lack of physical activity, unhealthy eating habits, tobacco and alcohol use, are present in many people already in adolescence, which later leads to the development of cardiovascular diseases. It was found that adolescence and young adulthood are the period of final formation of the ecological orientation of the individual, formation of econormative or ecodeviant behavior.Conclusions. It was determined that the majority of young people have a lack of need for a healthy lifestyle and the observance of positive environmental behavior, lack of knowledge in this field, low activity when fulfilling the requirements of a healthy lifestyle, irrational organization of educational activities, bad habits, etc. factors that negatively affect their health. The level of environmental concern among students in Ukraine and neighboring countries is comparable to that of underdeveloped countries, whose population is ecologically concerned mainly with local problems.
Keywords: youth health; healthy lifestyle; health-forming habits; environmental habits; environmental education